The Unique Strategy in Digital Cooperatives to Increase Benefit for Members - Ermaya, Sir Kalifatullah; Ermaya, Husnah Nur Laela; Azhar, Shofwan; Mulyana, Iwan (International Journal of Business, Economics, and Social Development, 2023)
The focus of this research is to analyze the uniqueness of the strategy in the cooperative business to increase profits for its members. This research is qualitative and descriptive. This research was conducted on 10 healthy cooperatives that have used digital applications in their daily operations registered in department of cooperatives and SMEs. The purpose of cooperatives is to prosper members and provide benefits either directly or indirectly. Some of the cooperative business uniqueness, namely: open and voluntary membership, democratic management system and the distribution of residual income is carried out fairly according to the business services of each member.From the results of study, the obstacles that occured in the implementation of digital cooperatives were: low capital provided by members, the lack of technology understanding in human resources, weak soft and hard skills, the existence of strong competition with other businesses, low interest in young people towards cooperative business, the low quality of the cooperative business planning.Revitalization is urgently needed so that cooperatives do not get worse. The authors suggested that cooperatives needed to develop the right strategy in order to survive in the storm of economic competition. The governmenthad to provide financial assistance for human resource development and provide training for cooperative employees. In addition, it is necessary to revamp the digital business comprehension for young people as new generation so that they can focus more on developing cooperative businesses for giving nation economic contribution.